Noninvasive Temperature Measurement in Dental Materials Using Nd3+, Yb3+ Doped Nanoparticles Emitting in the Near Infrared Region. (17th January 2020) - Yakovliev, Artem; Ohulchanskyy, Tymish Y.; Ziniuk, Roman; Dias, Tereza; Wang, Xin; Xu, Hao; Chen, Guanying; Qu, Junle; Gomes, Anderson S. L.
Abstract: In this work, the application of near infrared (NIR)‐emitting NaYbF4 :1%Tm 3+ @NaLuF4 :30%Nd 3+ core–shell nanoparticles is reported for noninvasive probing and monitoring the temperature during photopolymerization of dental materials. When excited at 808 nm, the synthesized nanoparticles emit NIR photoluminescence (PL) with two distinctive peaks at 865 and 980 nm which correspond to radiative transitions from the doped Nd 3+ and Yb 3+ ions, respectively. Luminescence intensity ratio between these two bands is found to vary with temperature due to temperature‐dependent electronic excitation energy transfer between Nd 3+ and Yb 3+ ions at the core/shell interface. This finding allows luminescence ratiometric evaluation of the in situ temperature during photopolymerization of resin cement (doped with nanoparticles) in a veneer placement procedure. In addition, the NIR emission also enables PL imaging of the distribution of the adhesive under the veneer. The results highlight that rare‐earth ions–doped nanoparticles with both excitation and emission in the NIR spectral range are advantageous for both PL‐based nanothermometry and imaging due to the reduced attenuation of NIR light by dental ceramics. Abstract : Near infrared (NIR) photoluminescent NaYbF4 :1%Tm 3+ @NaLuF4 :30%Nd 3+ core–shell nanoparticles are synthesized and applied for noninvasive measurement of temperature during photopolymerization of dental materials in situ. Similar rare‐earth ions–doped nanoparticles can be applied in dentistry not only as luminescent nanothermometers, but also as NIR imaging probes and upconverters of NIR to blue light for in situ photopolymerization.